2018
DOI: 10.1080/02640414.2018.1459153
|View full text |Cite
|
Sign up to set email alerts
|

“Good, better, creative”: the influence of creativity on goal scoring in elite soccer

Abstract: This study investigated the level of creativity of goals scored in football. Therefore, all goals in the Football FIFA World Cup 2010 and 2014, as well as the Football UEFA Euro 2016 were qualitatively examined. Three Football experts evaluated the last eight actions before each goal using a creativity scale ranging from 0 to 10 (0 = not creative, 10 = highly creative) of all goals scored via open play (311 goals in 153 matches). Level of creativity was revealed using an Analysis of Variance and the frquency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 21 publications
1
35
0
5
Order By: Relevance
“…Several empirical research reports demonstrate that creativity is a key factor for success in soccer performance. Kempe and Memmert (), for example, recently investigated the level of creativity of goals scored in the FIFA World Cup 2010 and 2014, likewise in the UEFA Euro 2016. This study revealed that teams that advanced to the later rounds of the competition showed greater creativity (as assessed by soccer experts) than less successful teams.…”
Section: Introductionmentioning
confidence: 99%
“…Several empirical research reports demonstrate that creativity is a key factor for success in soccer performance. Kempe and Memmert (), for example, recently investigated the level of creativity of goals scored in the FIFA World Cup 2010 and 2014, likewise in the UEFA Euro 2016. This study revealed that teams that advanced to the later rounds of the competition showed greater creativity (as assessed by soccer experts) than less successful teams.…”
Section: Introductionmentioning
confidence: 99%
“…Con respecto al terreno de juego (regla 1.1, Tabla 2), se decidió mantener las dimensiones totales, principalmente con dos propósitos. Primero, para que los jugadores de minibalonmano playa en ataque dispongan de espacios libres de defensas, que les permitan finalizar el ataque con lanzamientos a portería (Kempe & Memmert, 2018). Segundo, para que los jugadores no se vean sometidos a constreñimientos espacio-temporales y puedan tomar decisiones más apropiadas a la situación de juego (Coutinho et al, 2020).…”
Section: Discussionunclassified
“…In our case, the ARMF in these games distributes a significant amount of balls to the midfielder on the opposite side, supposedly in order to change the direction of the game, which is not as common when possession is not so important for the team, when they may give their possession to the other team because they are ahead on the scoreboard. and frequently at the usual areas from which to shoot, which are usually occupied by the top players (Kempe & Memmert, 2018). The aforementioned authors, after studying the Football FIFA World Cup of 2010 and 2014, found that the closer the actions that generated an opportunity to shoot at goal, the more creative they were.…”
Section: Discussionmentioning
confidence: 99%